Engajamento em fantasia e amigos imaginários: perspectivas dos pais e relações com teoria da mente, função executiva e linguagem - Velludo, Natalia Benincasa (2021)
In Brazil, there are several studies on symbolic play, however, only a few are focused on investigating high engagement in fantasy, as in lasting and elaborate forms of pretend play – in particular, the creation of imaginary companions and pretend identities. The present work aimed, therefore, to contribute in this direction by investigating the nature of these two forms of pretend play, as well as by testing possible correlations between high engagement in pretend play, theory-of-mind development and executive functions. Based on evidence of positive and negative associations of these elaborate forms of fantasy, a second goal was to investigate the attitudes of preschoolers’ parents on their possible pretend creations. In the first exploratory study, eight 3-year-olds (Mage = 43,4 mos; SD = 1,6 mo) were assessed by a receptive vocabulary test (PPVT), by the Theory-of-Mind Scale and by four executive function tasks. Children were also interviewed in order to obtain data on their predisposition to imagination, the creation of imaginary companions (or not) and personification. Moreover, five caregivers (one father and four mothers) participated in this first study and filled a questionary including questions about their children’s preferences in different contexts (e.g., favorite toys, stories, TV shows and play) and questions regarding the sociodemographic characteristics of participants (e.g., parents’ education level and occupation, number of family members). Non-parametric statistical analyses revealed that children’s performance was not different from chance on the EF tasks; it was below chance on the theory-of-mind scale and, consequently, no significant differences were found between the group of children classified as having high or low fantasy engagement. Results from this first study pointed to the need for important methodological changes, in particular, the change to another age group (4- and 5-year-olds) and an increase in sample size in order to find greater variability in terms of fantasy engagement level. In Study 2, 44 children (Mage = 58,9 mos; SD = 6,8 mos) participated, 25 girls and 19 boys. As a result of the Covid-19 pandemic, part of the data was collected in person and part by means of online forms and meetings on the Google Meet platform. The same instruments used in Study 1 were used in the first phase of data collection (in person). However, after the beginning of the pandemic, in order to guarantee that the online sessions with the children were not tiresome, three changes were made: a) only the first five out of the seven tasks in the theory-of-mind scale were used; b) the PPVT was excluded because of time requirements; and c) the Bear/Dragon EF task was excluded because 4-year-old participants (first phase of data collection) had performance suggesting a possible ceiling effect. Preliminary analyses did not indicate significant effects of gender, age and type of data collection (in person x online). Spearman correlation tests revealed significant associations between theory of mind and fantasy orientation level, but the effect size was weak; between the score on the Bear/Dragon task and on the Less is More task; between performance on the Bear/Dragon task and PPVT scores; and between performance on the Less is More task and PPVT scores. The level of fantasy engagement, based on data from children’s interviews, correlated significantly with the creation of imaginary companions and the predisposition to imagination and preferences (PIP-Child). Consistent with results from previous studies, there are different points of view from parents, varying from a balanced perception of the phenomenon, including both positive and negative aspects of high engagement in fantasy (41,7%) to an extremely positive view (29,2%). Only one participant showed and extremely negative attitude (4,2%). Together, results from these two studies point to the challenging aspect of the task of assessing different forms and levels of fantasy engagement. The present work included several measures of sociocognitive development and fantasy engagement, revealing significant associations between some measures that need to be further explored in future studies. At the same time, data obtained in the interviews with parents/caregivers suggests that maybe the mistaken belief that the creation of imaginary companions and other elaborate manifestations of fantasy are indicative of behavior and/or emotional problems may be weakening. On the other hand, more studies, as the one reported here, are needed so we can reach a better understanding of all the functions and benefits of pretend play to child development.